On Lukasiewicz Disjunction and Conjunction of Pythagorean Fuzzy Matrices - Venkatesan, D; Sriram, S (International Journal of Computer Sciences and Engineering, 2019)
In this paper, the algebraic properties of two operations disjunction and conjunction from Lukasiewicz type over Pythagorean fuzzy matries are studied. Also, using the relation between disjunction and conjunction certain results are obtained using modal operators.